CANDIDA SPP. POSITIVE CULTURE IN PNEUMONIA PATIENTS: A SINGLE-CENTER STUDY AT A TEACHING HOSPITAL IN SURAKARTA - Maryani; Primaningtyas, Widana (Biomedika, 2026)
The presence of Candida spp. in respiratory samples has long been considered colonization. Although the prevalence of Candida spp. in respiratory samples is quite high, the true incidence of Pneumonia Candida is only around 0.23-0.4%. Nevertheless, Pneumonia Candida significantly increases morbidity and mortality. Data for this study were collected from medical records using observational analysis with a cross-sectional design. Samples were obtained from patients isolate from July 2023 to June 2024, diagnosed with pneumonia with culture results identifying Candida spp. Factors that may increase the risk of Candida spp. infection were then identified. Data were processed using regression analysis techniques to identify the most influential factors. The regression analysis revealed that the length of hospitalization, patient age, and the use of other invasive devices were significant risk factors (p= 0.07; p= 0.001; p= 0.015), respectively. The Nagelkerke N square of the multiple logistic regression test was 50.5%.The findings from the research indicated that the duration of hospitalization, patient age, and use of invasive equipment had an influence on the incidence of positive Candida spp cultures in pneumonia patients..